AN EARLY TO MIDDLE ORDOVICIAN SUCCESSION OF CONODONT FAUNAS AT MäEKALDA, NORTHERN ESTONIA - Viira V.; Mägi S.; Löfgren A.; Wickström J. (My University, 2001)
The Mäekalda section presents a c. 12 m thick succession of mainly limestones, dolomites and siltstones of late Tremadoc to late Llanvirn age, exposed on the eastern outskirts of Tallinn, northern Estonia. The condensed sequence is rich in well-preserved conodont elements that provide the basis for detailed biozonation. In the Baltoscandian zonation, beds from the upper Varangu Paltodusdeltifer Zone up to the lower Aseri Eoplacognathusfoliaceus Subzone have been identified. In all, the conodont faunas exhibit a close resemblance to Swedish faunas. Many intervals can also be compared with coeval strata in western Russia. The presence at some levels of representatives of Laurentian conodont lineages provides an unusual opportunity for correlating Baltoscandian sequences with sequences in North America, especially in the lower Arenig part of the succession. The middle Volkhov (upper middle Arenig) Paroistodusoriginalis Zone at Mäekalda is remarkably complete bearing in mind the highly condensed nature of the section as a whole. The details of this zone can be correlated with the equivalent intervals in Swedish sections. In the upper Volkhov–lower Kunda beds there is a considerable stratigraphic gap in the section, but the upper Kunda has provided an excellent series of successive populations of Eoplacognathus, indicating that in this part the section is virtually complete.
Keywords: Ordovician; Paleozoic::Ordovician; Палеозой::Ордовикская